The role of Strategic Communication as a Factor of Competitive Advantage for the Organization - Gutiérrez-Meneses, Rafael E. (EFIM Ediciones, 2022)
Organizations are currently looking for new sources of competitive advantages that allow them to survive in the market. One of these sources is strategic communication, which is why this research has sought to analyze and review the current state of the art in terms of organizational communication as a factor in the competitive advantage of the organization/company, defining the concepts that nurture the theory of communication, strategic communication and the relevance of this to ensure competitive advantage. Similarly, the communication models that are adapted to the needs of each company were established as strategic communication tools in the organization, but in which common and infallible elements can be identified; for this reason, a generic organizational communication model was structured based on the elements developed by the authors studied, which can serve as a basis for the construction of one’s own. Communication systems in the organization must consider that their basis is human interaction, so they cannot separate this component from their logic.